Improving Performance Employees of Poly Service Department Nahdatul Ulama Hospital Strategy (RSNU) Tuban - Hendra Suwardana (INNOVATION RESEARCH JOURNAL, 2023)
The determinant factor in improving employee performance in the face of competition is the human resource factor. All service organizations will face particular in the service or service sector. Likewise with Nadhlatul Ulama Tuban Hospital in maintaining its existence amid service competition with other hospitals against the community in Tuban Regency. The most appropriate way to test the performance results is to do research. The purpose of this study is to understand human resource management strategies in improving the performance of its employees. The research results showed data processing of factors can affect employee performance. It called individual factors, psychology and company. The value of spirit in RSNU Tuban is also quite influential on the strategy of improving the performance of its employees, because all forms of action taken are not independent of the value of the organization's struggle established and presented amid the community. The results of processing research data are IFAS (Internal Strategic Factors Analysis Summary) value found 3.45 and EFAS (External Strategic Factors Analysis Summary)value found 2.99. so it can be concluded that employee performance improvement strategy through improved human resource management can improve performance in the RSNU and be in the category of satisfactory.